Mechanical Performance of Concrete Incorporating Wastewater Treatment Sludge from Pet Bottle Washing Recycling Lines as Partial Cement Replacement - Saim, Batrisyia Fatini; Noor Amira Sarani; Mohd Khairy Burhanudin (Journal of Structural Monitoring and Built Environment, 2026)
This study focused on the effect of using wastewater treatment sludge from polyethylene terephthalate (PET) bottle washing recycling lines (PWLS) as a partial cement replacement in concrete production. The concrete was produced with a constant mix proportion by controlling the water-to-cement ratio and aggregate content. Thus, in this study, a total of 16 mix designs were produced using PWLS as a partial cement replacement of 1% and 5% of the cement mass, with water-to-cement ratios of 0.55 kg and 0.65 kg, and curing periods of 7 and 28 days. Slump tests were conducted to determine the fresh concrete workability, while density, water absorption, and compressive strength tests were conducted at 7 and 28 days after curing periods. As for the chemical composition characterization of PWLS, X-ray fluorescence (XRF) analysis was conducted. Design Expert software is being used to conduct a statistical analysis through analysis of variance (ANOVA) and numerical optimization. The incorporation of 1% PWLS as partial cement replacement achieved the highest mechanical properties, with a compressive strength value of 37.9 MPa at 7 days and a predicted value of 31.1 MPa at 28 days, while density of 1993.75 kg/m³, and water absorption of 2.126% with a desirability of 0.853. Hence, the key finding of this study showed that the PWLS contain 82.9% aluminum, iron, and silicon oxides, which confirm its suitability as a supplementary cementitious material. Therefore, the incorporation of 1% PWLS has achieved the optimum balance between mechanical performance and sustainable waste utilization, while 5% replacement significantly reduced its strength due to delayed hydration.